Manajement Power Plan Untuk Kinerja Komputer yang Optimal - Rahman, Rakhmadi; Nurfauzi, Muhammad Aqmal; Ramadhani, Alya (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Windows operating system is a crucial piece of software for running computers, responsible for tasks such as memory management, process control, and the coordination of software and hardware. As technology advances, heterogeneous computing, which involves using various types of computing units within a single system, is becoming more common. However, this development introduces new challenges in terms of efficient resource management. This research aims to optimize the performance of the Windows operating system in heterogeneous computing environments through intelligent resource management. An experimental method is used to test various optimization and resource management techniques, including comparisons between AMD Ryzen and Intel Core processors. The results of the research indicate that proper resource management can enhance the performance and efficiency of the operating system. By understanding the strengths and limitations of each type of processor, users can make better decisions in selecting hardware that meets their needs. The conclusions of this study provide insights into the importance of efficient resource management for improving system performance and efficiency.